2020
DOI: 10.1002/jso.25837
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pathway for enhanced recovery after surgery for gastric cancer: A prospective single‐center phase II clinical trial for safety and efficacy

Abstract: Background We aimed to evaluate the safety and efficacy of a clinical pathway (CP) for enhanced recovery after surgery (ERAS) in gastric cancer patients, including early oral feeding and discharge on postoperative day 4. Methods We performed a prospective, single‐center, phase II clinical trial. Based on proposed indications for an ERAS CP in our retrospective study, we enrolled 133 patients younger than 65 years who were undergoing minimally invasive subtotal gastrectomy. The primary endpoint was the ERAS CP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In summary, the implementation of a CP for oncological gastrectomy at our institution did not lead entirely to the results that were expected based on studies on gastrectomy CPs in Asian settings [32,33], and on studies on CPs for other procedures in abdominal surgery at our institution and in other settings [13,[34][35][36][37][38][39][40]. The reasons for this apparent difference in the efficacy of gastrectomy and other abdominal surgery CPs can only be speculated on.…”
Section: Discussionmentioning
confidence: 75%
“…In summary, the implementation of a CP for oncological gastrectomy at our institution did not lead entirely to the results that were expected based on studies on gastrectomy CPs in Asian settings [32,33], and on studies on CPs for other procedures in abdominal surgery at our institution and in other settings [13,[34][35][36][37][38][39][40]. The reasons for this apparent difference in the efficacy of gastrectomy and other abdominal surgery CPs can only be speculated on.…”
Section: Discussionmentioning
confidence: 75%
“…In this study, the hospital length of stay in the early feeding group was significantly lower than that in the LOF group. However, the complication rate was not found to be higher in the EOF group ( 38 ).…”
Section: Discussionmentioning
confidence: 76%
“…According to ERAS protocol, early oral intake can be initiated without any complications. Jeonget al reported that most patients could resume an oral diet within 1 or 2 days with conservative care, and no serious complication occurred that was associated with early oral nutrition, such as aspiration or anastomosis leakage [ 13 ].Jie Ding et al reported that in meta-analysis studies, a reduction in time to first flatus is an important part of ERAS [ 16 ].Rohck et al achieved their goal of early oral feeding and discharge on the 4th day after surgery in 127 patients with stage 1 and 2a gastric cancer, with a rate of 77% [ 17 ]. Li et al determined that ERAS did not prolong the time to first flatus and did not increase complication rate in their eight RCT and meta-analysis series consisting of 400 cases [ 18 ].Liayang et al reported in their prospective study consisting of 98 cases that oral clear water on post-operative day 1 was accommodated by 86% of patients, oral liquid diet on post-operative day 2 was accommodated by 70% of patients, and oral semi fluid diet on post-operative day 3 was accommodated by 60% of patients [ 6 ].…”
Section: Discussionmentioning
confidence: 99%